Teaching Islamic Law in a Modern Secular Context: The Didactical Challenge - Mouez Khalfaoui (Presscience, 2026)
Despite earlier assumptions that it was an outdated discipline, Islamic law (Sharia) has experienced a significant academic renaissance over the last fifty years, notably within highly secularized, non-Muslim Western societies. This growing interest is driven not only by demographic changes but also by the global political relevance of Islamic legal discourse. Consequently, a critical challenge arises regarding how Islamic law can be detached from its original Muslim-majority context and adapted for research and teaching in secular European environments. This article analyzes the didactic and methodological approaches to teaching Islamic law in secular Western societies. It aims to bridge premodern Islamic teaching traditions with contemporary European educational concepts. The study posits that while Sharia cannot serve as a binding legal reference in secular democracies, it provides valuable moral and ethical contributions for addressing contemporary social challenges. The study adopts a narrative research approach, combining historical and analytical interpretations of classical Islamic pedagogy with contemporary secular teaching paradigms. It examines premodern didactic practices, such as the ḥalaqa (study circles), ʾijāza (scholarly authorization), munāẓara (debate), ʾimlāʾ (dictation), and mukhtaṣar (textual abridgment). The integration of Islamic law into modern German universities serves as the primary case study, enriched by the author’s empirical experience teaching in both Muslim-majority and European contexts. The historical analysis reveals that the pedagogy and didactics of Islamic law are dynamic and have continuously evolved, rather than being fixed concepts. While the traditional madrasa system and classical methods are often stigmatized today as authoritarian or purely teacher-centered, they possessed sophisticated epistemological functions in their historical contexts. To teach Islamic law effectively in modern secular environments, these traditions must be methodologically adapted. The study concludes that problem-oriented and solution-oriented learning approaches are particularly well-suited for teaching Islamic law in Europe, offering an effective pedagogical framework that could also be beneficially applied back within the Islamic world.